2015
DOI: 10.1177/1479164114565629
|View full text |Cite
|
Sign up to set email alerts
|

Role of mitochondrial dysfunction in hyperglycaemia-induced coronary microvascular dysfunction: Protective role of resveratrol

Abstract: Microvascular complications are now recognized to play a major role in diabetic complications, and understanding the mechanisms is critical. Endothelial dysfunction occurs early in the course of the development of complications; the precise mechanisms remain poorly understood. Mitochondrial dysfunction may occur in a diabetic rat heart and may act as a source of the oxidative stress. However, the role of endothelial cell-specific mitochondrial dysfunction in diabetic vascular complications is poorly studied. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 38 publications
2
13
0
Order By: Relevance
“…Recent studies have reported that naringin can ameliorate mitochondrial dysfunction [20, 30, 31]. Mitochondrial dysfunction in diabetes mellitus is increasingly being seen as a key mechanism that leads to atherosclerotic complications in diabetes [32]. Our data revealed that naringin rescued the lowered OCR, basal respiration, ATP production, maximal respiration and respiratory reserve capacity in cells exposed to a high glucose concentration.…”
Section: Discussionsupporting
confidence: 63%
“…Recent studies have reported that naringin can ameliorate mitochondrial dysfunction [20, 30, 31]. Mitochondrial dysfunction in diabetes mellitus is increasingly being seen as a key mechanism that leads to atherosclerotic complications in diabetes [32]. Our data revealed that naringin rescued the lowered OCR, basal respiration, ATP production, maximal respiration and respiratory reserve capacity in cells exposed to a high glucose concentration.…”
Section: Discussionsupporting
confidence: 63%
“…Resveratrol could be useful to treat various diseases; for example, it has anti-cancer, anti-aging, anti-inflammatory effects, such as prolonging lifespan, which have been reported [ 13 ]. Resveratrol is known to activate both Nrf2 and SIRT1, and activation of these proteins by resveratrol is regulated by oxidative stress and mitochondrial biogenesis through increased antioxidant protein expression and PGC-1α deacetylation [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, hyperglycaemia in microvascular endothelial cells leads to mitochondrial dysfunction. Thus, resveratrol-mediated mitochondrial protection could be used to prevent long-term diabetic cardiovascular complications (32). Indeed, resveratrol's effect on metabolic health has received considerable attention in the last decade.…”
Section: Resveratrol In Metabolic Syndromementioning
confidence: 99%